Anti-Müllerian hormone concentration as an indicator of female general health status: a cross-sectional study. Issue 1 (January 2022) - Vanni, Valeria Stella; Quartucci, Antonio; Rebecchi, Agnese; Privitera, Laura; Limena, Alessia; Ventimiglia, Eugenio; Viganò, Paola; Candiani, Massimo; Salonia, Andrea; Papaleo, Enrico
Abstract: Research question: To evaluate the correlation between clinical and hormonal parameters and comorbidity burden in Caucasian women presenting for fertility treatment. Design: Monocentric cross-sectional study including a cohort of 3163 Caucasian women seeking medical care for fertility treatment. All patients underwent centralized laboratory testing for hormonal assessment. Complete clinical and laboratory data from the entire cohort were retrospectively analysed. Comorbidity burden score was assessed by the Charlson Comorbidity Index (CCI; categorized as 0 versus 1 versus ≥2). Results: Descriptive statistics and regression models tested the associations between clinical and laboratory parameters and CCI. Among the entire cohort of patients, a CCI = 0 was found in 2977 women (94.1%), and CCI = 1 and CCI ≥2 were found in 113 (3.6%) and 73 (2.3%) patients, respectively. Age ( P  = 0.009), gravidity ( P  = 0.001), anti-Müllerian hormone (AMH, P  < 0.001) and TSH ( P  = 0.003) values were significantly different among CCI groups. In regression models, age at presentation and AMH emerged as independent indicators of CCI ≥ 1. Age at presentation <36 years (odds ratio [OR] 1.742, 95% confidence interval [CI] 1.284–2.364) and an AMH concentration ≤2.3 ng/ml (OR 1.864, 95% CI 1.29–2.69) were the most informative cut-off values for CCI ≥ 1 in the study population. Conclusions: A younger age at presentation and lower AMH concentrations are significant independent indicators of decreased general health in women requiring clinical evaluation for fertility treatment. As observed for sperm parameters in men, AMH might serve as a proxy of women's general health status.